A política cambial como estratégia para o crescimento econômico de países em desenvolvimento: uma análise aplicada ao Brasil - Oda, Paula (2013)
Exchange rate is an important element in the economic growth process in developing countries. It is supposed that the maintenance of this rate at relatively undervalued and competitive levels generates economic stimulus necessary to promote this growth by enabling greater competitiveness in the international trade, capable of producing positive expectations in economic agents, stimulating productive investment, and industrial development. However, it will be noticed that the process of financial globalization has resulted in an increase of capital flows, leading to significant effects on exchange rates in developing countries, and reducing the ability of monetary authorities in theses countries to control the exchange rate. The adoption of a flexible exchange rate policy, as proposed by orthodox theories, ended up allowing that the increase of speculative capital flow toward the peripheral economies provoking an intense appreciation of these currencies. This appreciation harmed the process of economic growth in these countries by reducing competitiveness in the international market, favoring an increase in imports, and discouraging productive investment, which could lead to a change in the productive structure in a way to incentive the targeting toward primary-export activities. Analyzing the performance of the Brazilian economy in the period between 1999 and 2011, this tendency toward currency appreciation and its impact on economic performance is noticed, resulting in a moderate growth, below the level observed in its major competitors. The results observed in the Brazilian economy suggest the need for a more active exchange policy, in order to preserve the exchange rate in undervalued levels, in a way to promote stimulus to economic growth. However, it is important to highlight that the Brazilian exchange market presents a structure that encumbers interventions that aim to preserve an exchange rate that favors economic growth, whereupon the spot market suffers intense influence from derivatives markets strongly speculative. This peculiarity should be explored in the discussion for a strategy of economic growth supported by an undervalued exchange policy